Suplementação nutricional, pretensões e custo entre jovens do interior e litoral paulista experiêntes em treinamento resistido - Siqueira, Leandro Oliveira da Cruz [UNESP]; Pessôa Filho, Daltom Muller [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP]; Neiva, Cassiano Merussi [UNESP]; Bravo, Valter Akira [UNESP] (My University, 2012)
Objective and closed questions were applied to 15 - 21 years old individuals under regular resistance exercise practice and self-reported nutritional supplements users, approaching training practices, type of substance feed and socioeconomic characteristics. The data were treated by frequency around the mean value. Major difference was observed to the goal of improvement in physical fitness (Guaruja 21% and Bauru 9.6%), close to the muscle hypertrophic enhancements (Guaruja 22% and Bauru 19.2%), and health proposes (17.3%), which was only reported in the country city. The monthly employment with supplements was observed to be close to one hundred Real, in both regions (Guaruja 79% and Bauru 80%). Even, based on different purposes, the supplements feed practice was closed to the goals, showing a reliable referential of use, but done without appropriated professional care.

Questões objetivas e fechadas foram aplicadas em jovens entre 15 a 21 anos praticantes regulares de exercícios resistidos e usuários de suplementos nutricionais, abrangendo perguntas sobre a prática esportiva, substâncias utilizadas e características socioeconômicas do indivíduo. Os dados foram apresentados em torno da frequência média de ocorrência. A maior diferença foi quanto à motivação pela melhora do condicionamento físico (Guarujá 21% e Bauru 9,6%), sendo a intenção de aumento da massa muscular a resposta mais próxima (Guarujá 22% e Bauru 19,2%), e a ênfase na Saúde mais relatada no Interior (17,3%). Ambas as regiões empregam até cem reais mensais no consumo (Guarujá 80% e Bauru 79%). Mesmo com diferentes propósitos, o consumo atende às pretensões relatadas, evidenciando bom referencial sem, contudo, usá-los sob supervisão profissional.
Supplementary nutrition, intends, and costs between youth practitioners of resistance exercise living in country and coastal paulista cities
Keywords: Supplementary nutrition; Use practice; Resistance exercise; Youth; Financial apportion; Suplementação nutricional; Forma de uso; Exercício resistido; Jovens; Investimento financeiro